The Development of the Ideal Teacher's Personality Concept of Ibn Sahnun and Azzarnuji for the Integrity of Modern Education - Imam Alhakam Wicaksono; Triono Ali Mustofa; Aisha Bahaaeldin Eprahim Ali; Muthoifin (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
This research aims to develop the concept of the ideal teacher's personality in Islamic education through the integration of classical values proposed by Ibn Sahnun and Azzarnuji with the principles of modern Islamic education. In this context, the research highlights the importance of combining the classical intellectual heritage of Islam with contemporary approaches to create a profile of teachers who can meet the demands of the times while maintaining the moral and spiritual integrity taught by the Islamic tradition. This study uses a qualitative method with a descriptive-analytical approach. Data were collected through a literature review of the works of Ibn Sahnun and Azzarnuji, as well as an analysis of contemporary literature on modern Islamic education. In addition, in-depth interviews with Islamic education experts were also conducted to get a more comprehensive perspective. The results of the study show that the classical values such as example, sincerity, and wisdom taught by Ibn Sahnun and Azzarnuji are still very relevant and can be integrated with modern educational concepts such as professional competence, innovation, and a student-centred approach. The development of the personality of this ideal teacher not only strengthens the morality and spirituality of teachers but also improves the quality of learning that is adaptive to the changing times. The novelty of this study lies in an integrative model that combines classical and modern values, which has not been studied in depth before. The implication of this study is the need to prepare a curriculum and teacher training program that prioritizes a balance between the classical heritage of Islam and the needs of today's education so that it can produce teachers who are academically competent as well as noble in character.